Criteria to identify sedimentary sills intruded during deformation of lacustrine sequences. (July 2022) - Alsop, G.I.; Weinberger, R.; Marco, S.; Levi, T.
Abstract: Although sedimentary dykes have been widely reported across a range of settings, sedimentary sills have received somewhat less attention, perhaps due to the potential difficulties in identifying largely conformable intrusions within bedded sequences. Most outcrop descriptions of clastic intrusions are based on deep-water marine sequences, with few descriptions of sills in lacustrine settings. The recognition of sills in such settings is, however, important because lacustrine sequences are increasingly used as a record of palaeoseismic activity. The misidentification of sills that contain fragments and clasts of host stratigraphy with seismically-generated turbidites and debris flows, may lead to incorrect interpretations of palaeoseismicity. We use the Late Pleistocene Lisan Formation of the Dead Sea Basin as a case study, where laminated lake sediments preserve intricate relationships with sills. This permits us to not only establish a range of criteria used in the identification of sedimentary sills, but also examine relationships with adjacent seismically-triggered slumps and slides. Key criteria we use to recognise sills include marked changes in their thickness together with bifurcation and bridging geometries. Sills may be internally layered, contain lenses of breccia, together with aligned and folded clasts that may be truncated across upper sill contacts. Critical evidence for the interpretation of sills is also preserved along sharp but irregular upper contacts that erode and truncate bedding in the overlying host sequence. Minor apophyses and 'wedges' intrude both upwards and downwards from sills, while isoclinal recumbent 'peel-back' folds are created in host sediments by shear generated along the lower contacts of sills. We have undertaken anisotropy of magnetic susceptibility (AMS) analysis and find an oblate fabric that suggests flow and intrusion of sills along the strike of the slope, that may also help with their identification in bedded sequences. Sills form along detachments to both extensional and contractional deformation associated with seismically-generated slumps and mass transport deposits, together with sub-surface fold and thrust systems. High fluid pressures associated with injection of sedimentary sills may facilitate near-surface failure and downslope movement of the sedimentary pile. Graphical abstract: Image 1 Highlights: Key criteria are established that help identify sedimentary sills in lacustrine sequences. Sills are created by seismically-triggered increases in fluid pressure that also generated slope failure and mass transport deposits (MTDs). Sills intrude along downslope-directed detachments suggesting these structures formed rapidly in the sub-surface. AMS analysis distinguishes deposition fabrics in beds from oblate deformation fabrics in sills and indicates sills intrude parallel to the strike of MTD thrusts. Sills intruded above sub-surface deformation may be confused with sedimentary caps leading to misidentification and consequences for palaeoseismicity.